MP14: Prospective external validation of the Ottawa 3DY screening tool for the detection of altered mental status of elderly patients presenting to the emergency department. (15th May 2017) - Kim, B.; Salehmohamed, Q.; Stenstrom, R.; Barbic, S.; Barbic, D.
Abstract : Introduction: Altered mental status (AMS) and cognitive impairment are common problems in elderly patients presenting to the emergency department (ED). The primary objective of this study was to test the diagnostic accuracy of the Ottawa 3DY (O3DY) screening tool for the detection of AMS in the ED.Methods: This was a prospective cohort study conducted at an inner city, academic ED with an annual census of 85, 000 visits. Study investigators and trained research assistants screened and approached a convenience sample of patients for informed written consent. Patients completed the O3DY, Short Blessed Test (SBT) and Mini-Mental Status Exam (MMSE). Descriptive statistics using counts, medians, means and interquartile ranges (IQR) were calculated. Sensitivity and specificity of the O3DY compared to the MMSE were calculated in STATA (version 11.2).Results: We screened 163 patients for inclusion, 150 were eligible to participate, and 116 patients were enrolled in the final study. The median age of participants was 81 (IQR 77-85), 44.8% were female, and the most common pre-existing comorbidity was hypertension. The median ED LOS at the time of O3DY completion was 1:40 (IQR 1:34-1:46). Characteristics of patients eligible, yet who declined to participate, were similar to the study population. The sensitivity of the O3DY for AMS was 71.4% (95%CI 47.8-95.1), and specificity was 56.3% (46.7-65.9). Sensitivity of the SBT was 85.7% (67.4-99.9) and specificity was 58.3% (48.7-67.8). Inter-rater reliability for the O3DY (k=0.64) and SBT (k=0.63) were moderate.Conclusion: In a cohort of geriatric patients presenting to an inner-city, academic ED the O3DY and SBT tools demonstrate moderate sensitivity and specificity for the detection of AMS.